2014
DOI: 10.14260/jemds/2014/3077
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Histopathological Study of Acquired Palmoplantar Keratoderma in a Rural-Based Tertiary Hospital

Abstract: BACKGROUND: Palmoplantar keratodermas are a diverse group of dermatological disorders characterized by abnormal thickening of skin over palms and soles. It is classified into inherited and acquired disorders. A number of diseases have been implicated as the cause of this common and interesting group and not many studies have been done in the acquired subset of this disorder. We have undertaken this study for finding out the incidence of various etiological factors in a rural based tertiary hospital. OBJECTIVE:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
9
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
4
9
3
Order By: Relevance
“…This result was similar to other studies of Sandeep et al 10 (54%) and Mahajan et al 13 (64.63%). Similarly the study by Murthy et al also showed a male predominance of (62.35%) and male to female ratio was 1.3:1.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…This result was similar to other studies of Sandeep et al 10 (54%) and Mahajan et al 13 (64.63%). Similarly the study by Murthy et al also showed a male predominance of (62.35%) and male to female ratio was 1.3:1.…”
supporting
confidence: 93%
“…In the present study unilateral involvement was seen in case of fungal infection (12/13) which was similar to that seen by Chopra et al 12 In the present study itching was the predominant symptom in majority of cases (60%) followed by pain, seen in 44.00% of cases. This result was similar with the results of the study by Sandeep et al 10 where itching was the predominant symptom, followed by pain and fissuring (seen in 75% cases). Similarly the study by Murthy et al showed that itching was the most common presenting feature seen (seen in 43/85 patients).…”
supporting
confidence: 92%
See 3 more Smart Citations